Handling emotions, strategic skill in disruptive leadership - Verdugo Tapia, María Leticia (Posgrados de la División de Ciencias Económica Administrativas, 2021)
This work addresses own emotions and those of others, by business leaders from the city of Hermosillo, Sonora. The objective is to know the level of development of these skills, considering their relevance in the practice of leadership, characterized by a stellar empathy between leader and followers, which facilitates the implementation of innovation strategies in these times of COVID-19 , based on two hypotheses H1. Leaders have a higher level of perception and understanding of their emotions than of perception and understanding of the emotions of others. H2. Leaders have a higher level of self-regulation of their emotions than of the regulation of the emotions of others. The Rotterdam Emotional Intelligence Scale was used as an evaluation instrument, which measures Emotional Intelligence focused on oneself and on others. The results obtained support the hypotheses of a higher level of self-knowledge and self-regulation than those of the others. With these results, it is presented as a conclusion that there is a need for the development of the primary skills of Emotional Intelligence, aimed at achieving disruptive leadership.